2018
DOI: 10.1093/ntr/ntx277
|View full text |Cite
|
Sign up to set email alerts
|

Harm Perceptions of Menthol and Nonmenthol Cigarettes Differ by Brand, Race/Ethnicity, and Gender in US Adult Smokers: Results from PATH Wave 1

Abstract: Menthol cigarettes have been historically marketed with messages conveying lower harm than other cigarettes. Little is known about how contemporary adult menthol smokers perceive the harm of their usual brand, and potential differences by race, gender, and young adult versus older adult age group. After adjusting for other factors, menthol smokers were more likely than nonmenthol smokers to perceive their cigarette brand as more harmful than other brands. Further, the association between menthol smoking and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…However, other research findings are mixed; one study found that menthol smokers viewed menthol cigarettes as safer or less harmful than non-menthol cigarettes, 15 while another recent study found that menthol smokers were more likely to perceive their brand as more harmful than other cigarette brands. 35 Some menthol smokers may be smoking menthol under the incorrect assumption that they are a healthier option than nonmenthol cigarettes. 36 This is consistent in our respondent group that had lower menthol health perception scores among menthol smokers compared with non-menthol smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other research findings are mixed; one study found that menthol smokers viewed menthol cigarettes as safer or less harmful than non-menthol cigarettes, 15 while another recent study found that menthol smokers were more likely to perceive their brand as more harmful than other cigarette brands. 35 Some menthol smokers may be smoking menthol under the incorrect assumption that they are a healthier option than nonmenthol cigarettes. 36 This is consistent in our respondent group that had lower menthol health perception scores among menthol smokers compared with non-menthol smokers.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with decades of research that demonstrates the continued use of harmful tobacco use despite knowledge of health risks. 35 In contrast, non-menthol smokers that reported lower levels of accurate health perceptions were more likely to support a ban. This variation by menthol preference may reflect the menthol smoker's strong opinions to preserve their product choice and avoid decisions related to switching or quitting.…”
Section: Menthol Perceptions and Policy Ban Support -Rath Et Almentioning
confidence: 98%
“…The tobacco industry’s marketing of the health and medical benefits of menthols led to many consumers believing that menthol cigarettes were less harmful than nonmenthols ( Unger et al, 2010 , Richter et al, 2008 , Wackowski et al, 2010 , Kingsbury et al, May 2020 , Anderson, 2011 ). However, other studies have indicated that menthol smokers in fact believe menthol cigarettes are more harmful than nonmenthols ( Cohn et al, 2019 , Wackowski et al, 2018 ). Moreover, demographic factors such as age, gender and race may influence harm perceptions ( Cohn et al, 2019 , Allen et al, 2010 ).…”
Section: Introductionmentioning
confidence: 97%
“…However, other studies have indicated that menthol smokers in fact believe menthol cigarettes are more harmful than nonmenthols ( Cohn et al, 2019 , Wackowski et al, 2018 ). Moreover, demographic factors such as age, gender and race may influence harm perceptions ( Cohn et al, 2019 , Allen et al, 2010 ). Researchers have identified a need for studies examining associations between perceived harm of menthol cigarettes and quitting behaviors, such as making a quit attempt or using evidence-based cessation treatment ( Cohn et al, 2019 , Gundersen et al, 2009 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation